Outcomes of Percutaneous Transluminal Angioplasty for Central Vein Stenosis in Hemodialysis: A Literature Review - Ibrahim, Hilman; Muradi, Akhmadu; Limianto, Eka A (UI Scholars Hub, 2021)
Percutaneous transluminal angioplasty (PTA) is the mainstay treatment for central vein stenosis. However, the recurrent rate of the stenotic lesion after PTA remains high. Thus, we ran a review found on some databases. Out of thirteen articles, five articles were eligible and reviewed. Drug-coated balloon angioplasty, plain old balloon angioplasty, percutaneous transluminal angioplasty, and stenting angioplasty were discussed regarding the outcomes with a focus on interest to prevent the stenosis.